KEGAGALAN KETERLIBATAN POLITIK: DARI KESENJANGAN DIGITAL MENUJU KESENJANGAN DEMOKRASI - Abhipraya, Fairuz Arta; Cahya Widodo, Bambang Eka (JPP (Jurnal Politik Profetik), 2021)
Almost all political scholars have proven that Facebook has an important role in seizing the public’s political engagement in political campaign agenda. However, the differences in voter segmentation and the internet capacity do not make all cases are all the same phenomenon. This study used a mixed research method to find out the Facebook's role in shaping the online political engagement from the Bantul community to the official accounts of candidates in Bantul Local Election 2020 for Bantul regency. The result of this research led to a conclusion that there was a digital divide that resulting in the democratic divide in the Bantul Regency. This democratic divide caused the lack of understanding of the local community towards the issue raised by the candidates. Furthermore, all the political candidates in the Bantul regency that competed in the local election 2020 had used symbolic issues for their political campaign agenda in this election such as religion-tolerance and other cultural-social issues.